Superhard sp2–sp3 hybrid carbon allotropes with tunable electronic properties - Meng Hu (AIP Advances, 2016)
Four sp2–sp3 hybrid carbon allotropes are proposed on the basis of first principles calculations. These four carbon allotropes are energetically more favorable than graphite under suitable pressure conditions. They can be assembled from graphite through intralayer wrinkling and interlayer buckling, which is similar to the formation of diamond from graphite. For one of the sp2–sp3 hybrid carbon allotropes, mC24, the electron diffraction patterns match these of i-carbon, which is synthesized from shock-compressed graphite (H. Hirai and K. Kondo, Science, 1991, 253, 772). The allotropes exhibit tunable electronic characteristics from metallic to semiconductive with band gaps comparable to those of silicon allotropes. They are all superhard materials with Vickers hardness values comparable to that of cubic BN. The sp2–sp3 hybrid carbon allotroes are promising materials for photovoltaic electronic devices, and abrasive and grinding tools.